Precipitação e aporte de nutrientes em diferentes estádios sucessionais de floresta Atlântica, Pinheiral - RJ - Diniz, Anderson Ribeiro; Pereira, Marcos Gervasio; Balieiro, Fabiano de Carvalho; Machado, Deivid Lopes [UNESP]; Menezes, Carlos Eduardo Gabriel (My University, 2013)
Forest cover has importance within the context of the water balance of a particular site and may alter the mechanism of entry of water and nutrients to the soil surface. The aim of this study was to quantify the net precipitation, interception, addition of nutrients in throughfall and stem flow in a forest in different stages of regeneration of Mata Atlântica: early-stage secondary forest (ESSF), intermediary stage secondary forest (ISSF) and advanced stage secondary forest (AESF). The study was conducted in Pinheiral, Rio de Janeiro state. The data collection was performed during the period of April 2009 to March 2010. The values of incident precipitation, effective precipitation and interception were similar among the three stages evaluated. The AESF area showed higher values of Mg and P in the addition of nutrients from throughfall compared with other areas assessed. The pH of the precipitation incident did not differ among areas, but was higher than the pH of rainfall. The three areas evaluated showed no difference in the addition of nutrients to flow coberthrough the trunk. The AESF area showed a trend of higher levels of addition of nutrients from throughfall precipitation and runoff from stemflow.
Precipitation and nutrient contribution in different successional stages of Atlantic forest, Pinheiral, Rio de Janeiro State
Keywords: Community ecology; Succession; Water balance